Improvement in quality of cow’s raw milk by using novel on-farm milk cooling system: Raw milk cooling system - Vekariya, Yogeshkumar; Patel, Dr. Sunil; Kathiriya, Mital (Indian Journal of Dairy Science, 2023)
The present study was conducted with an aim to check the improvement in raw milk quality at farm level by novel milk cooling system. Bulk milk cooler was taken as control. Optimization of different precooling temperatures viz., 30°C, 20°C, 10°C and 4°C in novel milk cooling system was carried out based on microbial and physicochemical tests. The raw milk samples were stored at 4°C and analyzed at an interval of 24 h for 72 h.  Significant (p